Uma abordagem para análise de desempenho de fluxos VoIP em redes de serviços diferenciados - Zuchowski Filho, Edmundo (2005)
This work presents a viability analysis of the use of a synthetic VoIP control flow to infer about the performance of individual flows of a flow aggregate belonging to an EF PHB in a DiffServ network. The proposed approach aims to establish a simple performance verification of SLA accomplishment related to the some of the VoIP flow requirements. The results should be used to feed requirements specifications for tool design, for example, to capacity planning activities and management actions. We classify the VoIP traffic as homogeneous (all flow packets created by a same codec type) and heterogeneous (packets originated from more than one codec type) to carry out the experiments. The experiments checked the hypothesis that the control flow performance can be somehow related to the performance of individual flows of a flow aggregate under the agreed assumptions and metrics. The metrics one-way delay, jitter and packet loss were evaluated by simulation for both homogeneous and heterogeneous traffic at several network-controlled load. The results let us conclude about the viability of the approach to evaluate one-way delay and with confidence limitations, also the jitter, depending on the traffic type (heterogeneous) and codec type.